“Sekolah Pasar” as an Effort to Revitalize Traditional Markets Become a Source of Economy and Learning Resources - Fitri Atur Arum; Dinik Fitri Rahajeng Pangestuti; Mun Yah Zahiroh; Hasan Al Banna (Journal of Islamic Economy and Community Engagement, 2022)
This study aims to find the best model to revitalize the market. The model designed in this study is expected to maintain the existence of traditional markets, improve technical and managerial human resource capabilities in managing markets, and achieve economic independence for traders. The method used in this research is Community Based Action Research, involving all stakeholders in the market which are packaged in the form of “Sekolah Pasar”. This method is carried out so that the model designed is the result of the elaboration and optimization of assets owned by the market in the form of physical assets, cultural assets, philosophical assets and assets in the form of skills. The result of this research is the design of a traditional market model that is in accordance with the potential of the market. The by-product of this research is an increase in the literacy and skills of market traders, traditional market curricula and value chain networks for markets.Keywords: Market School; Traditional Market; Market Revitalization